The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00006982-200007000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Herpesvirus Dna by Polymerase Chain Reaction in Ocular Fluids Obtained From Immunocompetent Patients

Abstract: The prevalence of herpesvirus DNA detectable by PCR techniques in ocular fluids appears to be quite low despite the high proportion of patients who tested positive for herpesvirus antibodies. Therefore, a positive result obtained in a patient presenting with vitreoretinal inflammation should be regarded as significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It is likely that with a larger test battery for foreign DNA, the yield of detection of specific infectious pathogens would be even greater. PCR from ocular fluids has a very high reliability with a very low false-positive rate [1316]. False negative results are more difficult to verify as there is no gold standard for the accuracy of PCR and viral or Toxoplasma gondii cultures are rarely performed [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that with a larger test battery for foreign DNA, the yield of detection of specific infectious pathogens would be even greater. PCR from ocular fluids has a very high reliability with a very low false-positive rate [1316]. False negative results are more difficult to verify as there is no gold standard for the accuracy of PCR and viral or Toxoplasma gondii cultures are rarely performed [17].…”
Section: Discussionmentioning
confidence: 99%
“…Two retinal diseases related to CMV infection were described in AIDS patients receiving HAART: classical retinitis and IRU that is related to a vigorous immune response to CMV ocular antigens [11, 12, 13]. IRU would occur in healed retina, due to an ocular inflammatory response to CMV antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Pendergast and associates reported that 75 aqueous and vitreous specimens from uninfected immunocompetent patients were negative for HSV 1 and HSV 2, VZV, CMV, and EBV by PCR. 8 The false-negative rate is more difficult to determine because often there is no other gold standard with which to compare, other than final clinical diagnosis, because viral cultures are among the least efficient diagnostic tests for intraocular fluid 9 and toxoplasmosis culture is performed rarely. 10 For this reason, validation in consecutive patients typical of those who usually undergo the testing is needed to assess the usefulness of the method for routine diagnostic use.…”
mentioning
confidence: 99%